1960
DOI: 10.1152/jappl.1960.15.3.418
|View full text |Cite
|
Sign up to set email alerts
|

Venous admixture in the pulmonary circulation of anesthetized dogs

Abstract: The venous admixture to the pulmonary circulation in the anesthetized dog was calculated from the O2. tension of the alveolar gas and arterial blood and the O2 content of the arterial and mixed venous blood when breathing 43 or 99% oxygen-nitrogen mixtures. The average shunt flow varies from 1–10% and averages about 5% of the total flow. When positive pressure breathing is applied the shunt flow is reduced in every animal and averages 1.0%. Indirect evidence suggests that the major part of this shunt reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0
1

Year Published

1967
1967
1988
1988

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(24 citation statements)
references
References 0 publications
3
20
0
1
Order By: Relevance
“…For the shunt calculations quoted in this paper a normal A-V difference of 5 vol.% was used (i.e., CVo2 = Cao2-5 vol.%). The oxygen consumption measurements recorded in this study were within the normal ranges; similar findings have been reported after open-heart surgery by Boyd, Tremblay, Spencer, and Bahnson (1959 (Finley et al, 1960;Riley and Cournand, 1951;Riley, Cournand, and Donald, 1951;Asmussen and Nielsen, 1960;Piiper 1961). This is illustrated in Table 1V.…”
Section: Sources Of Errorsupporting
confidence: 89%
See 2 more Smart Citations
“…For the shunt calculations quoted in this paper a normal A-V difference of 5 vol.% was used (i.e., CVo2 = Cao2-5 vol.%). The oxygen consumption measurements recorded in this study were within the normal ranges; similar findings have been reported after open-heart surgery by Boyd, Tremblay, Spencer, and Bahnson (1959 (Finley et al, 1960;Riley and Cournand, 1951;Riley, Cournand, and Donald, 1951;Asmussen and Nielsen, 1960;Piiper 1961). This is illustrated in Table 1V.…”
Section: Sources Of Errorsupporting
confidence: 89%
“…The solubility coefficient for dissolved oxygen was taken as 0-003 vol.% mm. Hg (Finley, Lenfant, Haab, Piiper, and Rahn, 1960). Oxygen capacity was assumed to be 20 vol.% unless the packed cell volume was below 40% or above 50%.…”
Section: Sources Of Errormentioning
confidence: 99%
See 1 more Smart Citation
“…These assumptions may not be invariably correct, but they are reasonable approximations which have been made by others (24,37,38). We have experimental evidence that the A-V 02 difference did not change significantly from room air to 100% oxygen breathing during the cardiac catheterization study (P > 0.6).…”
Section: Discussionmentioning
confidence: 60%
“…The result of CPAP is a rise in arterial Po2 and a fall in pulmonary shunting, the rise in Paoz being directly proportional to the reduction in the amount shunt, which is in turn inversely proportional to the FRC. x~, 16 The greater the amount of shunting across the lung, the more marked will be the effectiveness of PEEP therapy, so long as the shunt is due primarily to alveolar collapse rather than to diffusion block (alveolar--capillary block) seen in diffuse interstitial processes.IT In patients on ventilators a higher tidal volume is needed (12 to 15 cc/kg 18) to decrease shunting and to improve arterial hypoxaemia. Higher airway pressures are needed to maintain such a high tidal volume on a volume respirator.…”
Section: Discussionmentioning
confidence: 99%